Cross-Border Coordination of Prudential Supervision and Deposit Guarantees. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The scramble to expand deposit guarantees in Europe in response to recent financial turmoil confirms that the on-going integration of European financial markets requires closer coordination of prudential policies and financial safety nets. We study the optimal design of prudential supervision and deposit guarantee regulations in a multi-country, integrated banking market such as the European Union, where policy-makers have either similar or asymmetric preferences regarding profitability and stability of the banking sector. The paper concludes with recommendations on policy priorities in this area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet